Impact of Chronic HIV/SIV Infection on T Follicular Helper Cell Subsets and Germinal Center Homeostasis - Graff-Dubois, Stéphanie; Rouers, Angeline; Moris, Arnaud (Frontiers in Immunology, 2016)
The discovery of broad and potent HIV-1 neutralizing antibodies (bNAbs) has renewed optimism for developing an effective vaccine against HIV-1. The generation of most bNAbs requires multiple rounds of B cell receptor (BcR) affinity maturation, suggesting a crucial role of follicular helper T (Tfh) cells in their production. However, less than 1% of HIV-infected patients develop bNAbs that arise late in the course of infection, indicating probable Tfh and B cell dysfunctions in this context. Since the last few years and despite their low abundance, Tfh cells have been studied in the lymph nodes and spleen of individuals with HIV infection and of macaques experimentally infected with SIV. Various lymphoid Tfh cell subsets have been characterized, including pre Tfh (pTfh), germinal center Tfh (GC Tfh) and the regulatory counterpart of Tfh cells, the so-called follicular regulatory T (Tfr) cells. The latter have been reported to play a crucial role in the control of T and B cell crosstalk and germinal center reactions. More recently, circulating Tfh-like cells (cTfh) have been identified. Meanwhile, advances in single-cell technologies have made possible to analyze the transcriptional profiles of low abundant cells such as Tfh populations. Using transcriptional signatures, we review here the impact of chronic SIV/HIV infection on Tfh, GC Tfh, pTfh and cTfh differentiation and helper T cell functions with regard to their capacity to induce efficient B cell maturation. We will explore some hypothesis to explain the increased proportion of Tfh cells reported in chronically infected individuals and the impact on HIV pathogenesis.